Medicinal plants of the Iban community at Kampung Sebubu Saratok, Sri Aman - Albert, Kuin. (Universiti Malaysia Sarawak (UNIMAS), 2005)
A study on medicinal plants was carried out at Kampung Sebubu to document its uses among the Iban community. Thirty species of medicinal plants from 29 genera and 25 families with one species are unidentified were collected and documented. The specimen collected were preserved and kept at Universiti Malaysia Sarawak Herbarium (HUMS). Most of the medicinal plants are used for treating eye infections. shingles, abscesses, body pain, fungal infection, stop flatulence, stop bleeding, reduce high blood and others. Out of 30 species, 10 species were tested for the presence of alkaloid, flavonoid and saponin using their leaves or all part of specimen. The preliminary phytochemical analysis showed that all the 10 species contained alkaloid. Among the species that showed strong positive presence of alkaloid is Lasianthus sp., Premna cordi/olia Roxb.and Uncaria acida (Hunt.) Roxb. (+++). In saponin testing, it showed that Nephrolepis biserrata SW. Schoot and Alstonia scholaris (L.) R.Br. had a high saponin contents (+++). Vitex pubescens Vah!., Ficus grossulariodes Burm.fand Phaenthus splendens Miq are have less of saponin (+). All of the species tested showed the present of flavonoid except Lasianthus sp., Vi/ex pubescens Vahl and Kemedu.